Public Private People Partnership (4ps) in Waste Management Services: A Review of Efficiency and Effectiveness - Zuhdi, Sulaiman; Saputra, Trio; Dailiati, Surya; Hernimawati, Hernimawati (Universitas Padjadjaran, 2024)
This study aims to evaluate the efficiency and effectiveness of waste management services in Pekanbaru through the role of partnerships between the government, the private sector, and the community. Qualitative methods with case studies were applied in this research. Data were collected through observation, in-depth interviews, and document analysis. Data analysis through thematic coding. Triangulation were conducted to verify the findings by comparing data from various sources and ensuring consistency of results. The results of the study indicated that the efficiency and effectiveness of waste management services are highly dependent on synergy between stakeholders, transparency of information, and collective efforts. The waste bank and composting programs have been proven to reduce the volume of waste that needs to be managed, accelerate the recycling process, and extend the operational period of the Final Disposal Site (FDS). However, although partnerships with the private sector and growing community participation are important solutions, there are still obstacles to sharing information, community understanding, and collective responsibility and communication mechanisms. For this reason, the city government needs to build more effective and interactive communication channels through digital-based complaint applications and information services that enable two-way feedback.